RENDAHNYA MOTIVASI SISWA MADRASAH TSANAWIYAH DALAM PEMBELAJARAN BAHASA ARAB SECARA DARING - Kamila - Nadawiyah (Taqdir, 2021)
Since the COVID-19 pandemic entered Indonesia, the government has begun to impose restrictions in all sectors, including the education sector. From kindergarten to college level, all students learn online at home. Online learning certainly has a very influential impact on teachers and students in the teaching and learning process, especially for middle-level students who still need supervision in carrying out learning. Online education greatly influences students' motivation in learning, especially Arabic lessons that are classified as difficult subjects. The method used in this study is descriptive qualitative method, the object of this study is the student's psychological motivation, while the subject of this study is a first-class student based on Islam. From the data found that students tend not to have motivation in learning Arabic because of the absence of friends for discussion and lack of environmental support. To respond to this, creative methods are needed in the learning process and it takes support from parents to keep an eye on and provide positive support for students.